Pengaruh CAR, NPF, FDR dan BOPO terhadap Profitabilitas BPRS di Indonesia - Irma Rizky Destiani; Ine Mayasari; Destian Arshad Darulmalshah Tamara; Setiawan Setiawan (Journal of Applied Islamic Economics and Finance, 2023)
This study aims to determine the effect of Capital Adequency Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Efficiency Ratio (OER) on profitability as measured by Return On Assets (ROA) and Return On Equity (ROE) at Sharia Rural Banks in Indonesia for the 2014-2021 period. This research uses multiple linear regression analysis method. The data used is secondary data, namely Islamic banking statistics that have been published on the official page of the Financial Services Authority (OJK). The results of this study conclude that CAR and NPF have no effect on ROA. Furthermore, FDR has a positive effect on ROA while BOPO has a negative effect on ROA. Then CAR has a positive effect on ROE. Furthermore, NPF and FDR have no effect on ROE, while BOPO has a negative effect on ROE.